Uma história institucional do Centro Tecnológico do Exército (1979-2013) - Queiroz, Claudete Fernandes de (2015)
This work tells the story of the creation and the institutional development of the Army Technology Center (CTEx), dedicated to the research and development on military use of materials in the Brazilian Army. The aim of this study is to analyze the origin of this institution, the reasons for its creation and the role of the main actors involved, as well as present the main projects developed in CTEx. Initially, we analyze the field of Science and Technology in Brazil between 1960 and 1980, and then deepen fundamental aspects of the history of CTEx between 1979 and 2013. Finally, one presents the results obtained from interviews with 26 (twenty-six) servers (military and civilian) working mainly with research and development in CTEx